INTRODUCTION OF DOUBLE-ENTRY BOOKKEEPING INTO JAPAN. - Shimme, Shinshichiro (The Accounting Review, 1937)
There are various methods of book keeping prevalent in the world, each requiring a specific technique. For instance, there are Italian, English, German, French and American bookkeeping methods in accordance with conditions peculiar to the country. In reviewing the introduction of double-entry bookkeeping into Japan, it will be best to differentiate between the introduction of the technique of double-entry bookkeeping and the importation of literature on book-keeping. The introduction of technique will be dealt with first. The introduction of the technique of double-entry bookkeeping may be said to have occurred in the latter part of the Tokugawa Shogunate. All the merchants in Japan in the Tokugawa Era were using single-entry bookkeeping. However, the Japanese "Industrial Revolution," which took place during the latter part of the Tokugawa Shogunate and during the Meiji Restoration, indicated the importance of European machinery and equipment and the industrial system gradually adapted itself to the European mode. Accounting for business transactions had become so complicated that the hereditary Japanese system could hardly do justice to the new business methods, so considerable impetus was given to the introduction of European accounting methods.